Subspecialisation in cardiology care and outcome: should clinical services be redesigned, again?. Issue 2 (February 2016) - Pathik, B.; De Pasquale, C. G.; McGavigan, A. D.; Sinhal, A.; Vaile, J.; Tideman, P. A.; Jones, D.; Bridgman, C.; Selvanayagam, J. B.; Heddle, W.; Chew, D. P.
Abstract : Background: Inpatient management of cardiac patients by cardiologists results in reduced mortality and hospitalisation. With increasing subspecialisation of the field because of growing management complexity and use of technological innovations, the impact of sub‐specialisation on patient outcomes is unclear. Aim: To investigate whether management by subspecialty cardiologists impacts the outcomes of patients with subspecialty‐specific diseases. Methods: All patients admitted to a tertiary centre over nine years with a diagnosis of heart failure, acute coronary syndrome (ACS) or primary arrhythmia were reviewed. The outcomes of these patients managed by cardiologists subspecialised in their admission diagnosis (heart failure specialists, interventionalists and electrophysiologists) were compared with those treated by general cardiologists. Results: Heart failure was diagnosed in 1704 patients, ACS in 7763 and arrhythmia in 4398. There was no difference in length of stay (LOS) ( P  = 0.26), mortality ( P  = 0.57) or cardiovascular readmissions ( P  = 0.50) in heart failure patients treated by general cardiologists compared with subspecialists. In ACS patients, subspecialty management was associated with reduced LOS, cardiovascular readmissions and mortality (all P  < 0.05). This reduction in mortality was seen mainly in lower risk patients ( P  < 0.05). There was a reduction in LOS and cardiovascular readmissions in arrhythmia patients receiving subspecialty management (both P  < 0.05) but no difference in mortality ( P  = 0.14). ACS patients managed by interventionalists were more likely to undergo coronary intervention ( P  < 0.05). Electrophysiologists more frequently referred patients for catheter ablation and pacemaker implantation than general cardiologists ( P  < 0.05). Conclusions: The benefits of subspecialty care seem attributable to the appropriate selection of patients who would benefit from technological innovations in care. These results suggest that the development of healthcare systems which align cardiovascular disease with the subspecialist may be more effective.